PENENTUAN KADAR DAN VALIDASI METODE SPEKTROFOTOMETRI ULTRAVIOLET PADA SEDIAAN TABLET BROMHEKSIN DARI BEBERAPA INDUSTRI FARMASI - Miswanda, Dikki; Ridwanto, Ridwanto; Mulyani, Riski (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Bromhexine works by increasing the amount of mucus and reducing its viscosity. In Pharmacopoeia Edition V (2014) there is no monograph of bromhexine either in syrup form or in tablet preparation. Bromhexine has chromophore and auxochrome groups in its structure so that this compound can absorb radiation in the ultraviolet (UV) region. The purpose of this study is to find an alternative method that is simple and inexpensive but provides good accuracy and precision. This method was validated and then the validated method was applied to the assay of bromhexine tablets on the market. The method used was ultraviolet spectrophotometry with 0.1 N HCl as a solvent. The sample used was 5 bromhexine tablets with trade names. The validation test parameters carried out are accuracy, precision, detection limits and quantitation limits. The results of the specified validation test provide an accuracy test with a percent recovery of 101.14% and a Relative Standard Deviation (RSD) of 1.6964%. This shows that this method provides good accuracy and precision, with a limit of detection (LOD) of 0.6315 and a limit of quantitation (LOQ) of 1.1983. The assay results of the tablet sample of the trade name Bisolvon (PT. Boehringer Ingelheim) 100.70% -+ 0.56%; Bromifar (PT. Ifars) 101.09% -+ 0.44%; Bronchitis (PT. Graha Farma) 100.65% -+ 0.67%; Mucohexin (PT. Sanbe) 100.92% -+1.25% and Omesolvon (PT. Mutifa) 100.34% -+ 0.37%. All tablets determined to meet the requirements of the general content of a tablet that is not less than 90% and not more than 110% of the amount stated on the label.